The Mexican border cities : landscape anatomy and place personality - Arreola, Daniel D. (Daniel David), 1950- (University of Arizona Press, 1993)
Considers border cities, as "Mexican places modified by American influences," from the perspectives of urban morphology, and the urban built environment. Examines 18 settlements from towns of less than 10,000 to cities of nearly a million people. The authors contend that despite their proximity to the US, these cities remain essentially Mexican. More than 75 maps and b & w photos.